Obstetric brachial plexus injury - Mukund R Thatte; Rujuta Mehta (Indian Journal of Plastic Surgery)
Obstetric brachial plexus injury (OBPI), also known as birth brachial plexus injury (BBPI), is unfortunately a rather common injury in newborn children. Incidence varies between 0.15 and 3 per 1000 live births in various series and countries. Although spontaneous recovery is known, there is a large subset which does not recover and needs primary or secondary surgical intervention. An extensive review of peer-reviewed publications has been done in this study, including clinical papers, review articles and systematic review of the subject. In addition, the authors′ experience of several hundred cases over the last 15 years has been added and has influenced the ultimate text. Causes of OBPI, indications of primary nerve surgery and secondary reconstruction of shoulder, etc. are discussed in detail. Although all affected children do not require surgery in infancy, a substantial proportion of them, however, require it and are better off for it. Secondary surgery is needed for shoulder elbow and hand problems. Results of nerve surgery are very encouraging. Children with OBPI should be seen early by a hand surgeon dealing with brachial plexus injuries. Good results are possible with early and appropriate intervention even in severe cases.